2007
DOI: 10.1074/jbc.m609499200
|View full text |Cite
|
Sign up to set email alerts
|

H2O2-induced Kinetic and Chemical Modifications of Smooth Muscle Myosin

Abstract: The effect of H 2 O 2 on smooth muscle heavy meromyosin (HMM) and subfragment 1 (S1) was examined. The number of molecules that retained the ability to bind ATP and the actinactivated rate of P i release were measured by single-turnover kinetics. H 2 O 2 treatment caused a decrease in HMM regulation from 800-to 27-fold. For unphosphorylated and phosphorylated heavy meromyosin and for S1, ϳ50% of the molecules lost the ability to bind to ATP. H 2 O 2 treatment in the presence of EDTA protected against ATPase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…Oxidation of methionines by peroxide has been previously detected in isolated skeletal muscle actin (49,50), smooth muscle myosin subfragments (59), and calmodulin (26). Oxidation of cysteine residues has been detected in isolated myosin fragments treated in solution with peroxide (49,50,59) or peroxynitrite (86). In contrast, our study clearly showed that H 2 O 2 treatment of myosin in the muscle filament lattice does not affect myosin cysteines, particularly the most reactive, Cys707 (Fig.…”
Section: Comparison With Previous Studies Of H 2 O 2 Treatment Of Mussupporting
confidence: 42%
See 3 more Smart Citations
“…Oxidation of methionines by peroxide has been previously detected in isolated skeletal muscle actin (49,50), smooth muscle myosin subfragments (59), and calmodulin (26). Oxidation of cysteine residues has been detected in isolated myosin fragments treated in solution with peroxide (49,50,59) or peroxynitrite (86). In contrast, our study clearly showed that H 2 O 2 treatment of myosin in the muscle filament lattice does not affect myosin cysteines, particularly the most reactive, Cys707 (Fig.…”
Section: Comparison With Previous Studies Of H 2 O 2 Treatment Of Mussupporting
confidence: 42%
“…Oxidation of methionines by peroxide has been previously detected in isolated skeletal muscle actin (49,50), smooth muscle myosin subfragments (59), and calmodulin (26). Oxidation of cysteine residues has been detected in isolated myosin fragments treated in solution with peroxide (49,50,59) or peroxynitrite (86).…”
Section: Comparison With Previous Studies Of H 2 O 2 Treatment Of Musmentioning
confidence: 98%
See 2 more Smart Citations
“…Possible mechanisms contributing to this include NO-induced reduction in contractile agonist responsiveness, decreased catecholamine bioavailability due to conversion to less active forms by NO (18,25) or superoxide (19), cGMP-independent effects on agonist-receptor coupling (26,27), and oxidative effects converging on contractile proteins (28,29). Endotoxin-mediated shock is associated with low peripheral vascular resistance resistant to agents such as norepinephrine and epinephrine (3,14,38), an effect that is variably reversible with nonspecific NOS inhibitors (10).…”
Section: Discussionmentioning
confidence: 99%